História da ciência em aulas de química: o que revela a prática de professores? - Silva, Abílio Tomaz Coelho da (2012)
This dissertation presents a case study of ethnographic type about the use of History of Science in High School Chemistry classes at Uberlândia-MG. In order to choose the subjects of the research we applied fifteen questionnaires in six schools of this city. From the analysis of these questionnaires we chose two teachers that had their classes accompanied and recorded from April to June of 2011 and, after that the recordings were transcribed. We also verified some conceptions about science and about its teaching. The results demonstrated that the teachers have a varied range of concepts, from empiricist visions about science to the view that science knowledge is changeable. They used textbooks as their main source to prepare their classes and as consequence they use the History of Chemistry attached to the main subject as curiosities and biographies of some famous characters. The methodologies for this approach vary from the description of some experiments performed by some scientist to asking the student to search some biographical information about some characters such as Lavoisier and Proust.